2004
DOI: 10.1016/j.neuroimage.2003.09.041
|View full text |Cite
|
Sign up to set email alerts
|

Pausing for thought: engagement of left temporal cortex during pauses in speech

Abstract: Pauses during continuous speech, particularly those that occur within clauses, are thought to reflect the planning of forthcoming verbal output. We used functional Magnetic Resonance Imaging (fMRI) to examine their neural correlates. Six volunteers were scanned while describing seven Rorschach inkblots, producing 3 min of speech per inkblot. In an event-related design, the level of blood oxygenation level dependent (BOLD) contrast during brief speech pauses (mean duration 1.3 s, SD 0.3 s) during overt speech w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
44
1
12

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(65 citation statements)
references
References 46 publications
8
44
1
12
Order By: Relevance
“…The timing of the early differential positivity is consistent with the contention that goal activation occurs in anticipation of the stimulus on informatively cued trials. This fits nicely with the associated superior temporal gyrus activation, as this area is important for temporal action planning (Kirscher et al, 2004;Paulus et al, 2005), as well as for the generation of verbal task labels (Price, 2000) a process shown to be critical in task-switching literature (Goschke, 2000). The size of the RT benefit for informative relative to noninformatively cued trials was correlated with activity in the left superior PPC (Fig.…”
Section: Informatively Cued N Non-informatively Cued Contrastsupporting
confidence: 75%
“…The timing of the early differential positivity is consistent with the contention that goal activation occurs in anticipation of the stimulus on informatively cued trials. This fits nicely with the associated superior temporal gyrus activation, as this area is important for temporal action planning (Kirscher et al, 2004;Paulus et al, 2005), as well as for the generation of verbal task labels (Price, 2000) a process shown to be critical in task-switching literature (Goschke, 2000). The size of the RT benefit for informative relative to noninformatively cued trials was correlated with activity in the left superior PPC (Fig.…”
Section: Informatively Cued N Non-informatively Cued Contrastsupporting
confidence: 75%
“…Previous research has shown that at least in constrained description tasks (in which participants had to describe a path from picture to picture on a computer screen), L1 speakers are more likely to pause before lower frequency nouns in comparison to higher frequency nouns (Hartsuiker and Notebaert 2010;Kircher et al 2004). The current study showed that, in more spontaneous speech, both L1 and L2 speakers are more likely to pause before lower frequency nouns than before higher frequency nouns and that L2 proficiency did not modulate this effect.…”
Section: Discussioncontrasting
confidence: 51%
“…Taken together, our results suggest that listeners are sensitive to the increased likelihood of speakers to be disfluent when formulating low-frequency referents (Hartsuiker & Notebaert, 2010;Kircher et al, 2004;Levelt, 1983;Schnadt & Corley, 2006). Moreover, this sensitivity guides them to use disfluency as a cue to predict reference to a low-frequency object.…”
Section: Discussionmentioning
confidence: 52%
“…Instead of counterbalancing the two fluency conditions across the LF and HF filler targets, each LF filler target was recorded in the disfluent condition and each HF filler target was recorded in the fluent condition. The reason for this design was that we aimed at a fluent:disfluent ratio across the two frequency conditions which resembled the ratio in spontaneous speech (with disfluencies occurring more often before low-frequency words; Hartsuiker & Notebaert, 2010;Kircher et al, 2004;Levelt, 1983;Schnadt & Corley, 2006). Using our design, the fluent:disfluent ratio was 1:3 for low-frequency targets and 3:1 for high-frequency targets.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation